Pengaruh Teknologi Finansial, Kepercayaan dan Literasi Keuangan terhadap Inklusi Keuangan Masyarakat Desa Karangmukti Tasikmalaya - Syifa Fadillatunnisa Fauziah; Heidi Siddiqa (PT. Alahyan Publisher Sukabumi, 2026)
This study aims to examine the factors influencing financial inclusion in rural areas, particularly in Karangmukti Village, Tasikmalaya Regency. The main focus of this research is to analyze the influence of financial technology, financial literacy, and trust in increasing financial inclusion. This study used a quantitative approach with a cross-sectional survey design, with data obtained from 100 respondents aged 30–45 years and analyzed using multiple linear regression. The results show that financial technology, financial literacy, and trust have a positive and significant effect on financial inclusion, with trust being the most dominant variable. The research model has a coefficient of determination of 65.3%, indicating strong explanatory power for the dependent variable. These findings confirm that increasing financial inclusion in rural areas depends not only on digital infrastructure but also on psychological factors and individual financial management abilities. Thus, the results of this study have important implications for developing a more inclusive and sustainable digital financial ecosystem in rural areas.